Advanced Bioelectrical Signal Processing Methods: Past, Present and Future Approach-Part I: Cardiac Signals - Martinek, Radek; Ladrova, Martina; Sidikova, Michaela; Jaros, Rene; Behbehani, Khosrow; Kahankova, Radana; Kawala-Sterniuk, Aleksandra (Sensors (Basel, Switzerland), 2021)
Advanced signal processing methods are one of the fastest developing scientific and technical areas of biomedical engineering with increasing usage in current clinical practice. This paper presents an extensive literature review of the methods for the digital signal processing of cardiac bioelectrical signals that are commonly applied in today's clinical practice. This work covers the definition of bioelectrical signals. It also covers to the extreme extent of classical and advanced approaches to the alleviation of noise contamination such as digital adaptive and non-adaptive filtering, signal decomposition methods based on blind source separation and wavelet transform.
Keywords: srdce; počítačové zpracování signálu; Algorithms; Electrocardiography; Signal Processing, Computer-Assisted; Wavelet Analysis; biomedical signals; lidé; Heart; cardiac signals; fetal electrocardiography; electrocardiography; algoritmy; vlnková analýza; Humans; vectorcardiography; elektrokardiografie